11: Institutional strategies in the sharing economy: the case of ride-hailing and hospitality lodging in Brussels - Distelmans, Michaël; Scheerlinck, Ilse (Edward Elgar Publishing, 2026)
This chapter examines institutional strategies employed by Uber, Airbnb, and incumbent competitors. Entrepreneurs use institutional strategies to seek or preserve legitimacy by either changing or maintaining the institutional and regulatory setting. Using a two-fold case study design, based on data from content analysis and interviews, we compare institutional strategies across sharing economy ecosystems of ride-hailing and hospitality lodging. We also analyse how those strategies have shaped governance since sharing platforms’ entry in Brussels over a decade ago. The findings show that each ecosystem has its specific dynamics in terms of institutional strategies and governance.